Comparative effectiveness of onabotulinumtoxinA versus oral migraine prophylactic medications on headache-related resource utilization in the management of chronic migraine: Retrospective analysis of a US-based insurance claims database. (August 2016) - Hepp, Zsolt; Rosen, Noah L; Gillard, Patrick G; Varon, Sepideh F; Mathew, Nitya; Dodick, David W
Background: Migraine, especially chronic migraine (CM), causes substantial disability; however, health care utilization has not been well characterized among patients receiving different migraine prophylactic treatments. Methods: Using a large, US-based, health care claims database, headache-related health care utilization was evaluated among adults with CM treated with onabotulinumtoxinA or oral migraine prophylactic medications (OMPMs). Headache-related health care utilization was assessed at six, nine, and 12 months pre- and post-treatment. The primary endpoint was the difference between pre- and post-index headache-related health care utilization. A logistic regression model was created to test the difference between onabotulinumtoxinA and OMPM-treated groups for headache-related emergency department (ED) visits and hospitalizations. Results: Baseline characteristics were comparable between groups. The proportion of patients with ED visits or hospitalizations for a headache-related event decreased after starting onabotulinumtoxinA, but increased after starting an OMPM, for all three cohorts. Regression analyses showed that the odds of having a headache-related ED visit were 21%, 20%, and 19% lower and hospitalization were 47%, 48%, and 56% lower for the onabotulinumtoxinA group compared to the OMPM group for the six-month, nine-month, and 12-month post-index periods, respectively. Conclusions: When compared with similar patients who initiated treatment with OMPM, onabotulinumtoxinA was associated with a significantly lower likelihood of headache-related ED visits and hospitalizations.